2020
DOI: 10.21203/rs.3.rs-20557/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of continuous infusion of phenylephrine vs. norepinephrine on parturients and fetuses under LiDCOrapid monitoring: A randomized, double-blind, placebo-controlled study

Abstract: Background: Hypotension following spinal anesthesia (SA) during cesarean delivery (CD) occurs commonly and is related with maternal and fetal complications. Norepinephrine infusion is increasingly used for prevention of post-SA hypotension; however, its effects as compared to the traditional phenylephrine infusion remain unclear. This study aimed to compare the effects of phenylephrine and norepinephrine administered as continuous infusion during elective CD on maternal hemodynamic parameters and maternal and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Similar to the results from previous study with singleton pregnancy, infusion of norepinephrine was not associated with greater heart rate [10] or greater CO [15], in patients twin pregnancy receiving spinal anesthesia for cesarean delivery. Although the incidence of bradycardia was higher in patients receiving phenylephrine, the requirements of atropine were not different between the two vasopressors.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the results from previous study with singleton pregnancy, infusion of norepinephrine was not associated with greater heart rate [10] or greater CO [15], in patients twin pregnancy receiving spinal anesthesia for cesarean delivery. Although the incidence of bradycardia was higher in patients receiving phenylephrine, the requirements of atropine were not different between the two vasopressors.…”
Section: Discussionsupporting
confidence: 88%
“…In 2 other randomized trials comparing fixed-rate infusion of norepinephrine or phenylephrine with rescue vasopressor boluses, 7,21 no difference in CO between groups was observed. Of note, in these latter 2 studies, 7,21 CO was measured by pulse contour analysis of the arterial pressure curve, a method whose reliability is markedly altered by changes in arterial tone such as those obtained with vasopressor boluses. 24,25 In the former trial, 6 like in other studies, 4,26 SV was measured by suprasternal Doppler and showed a consistent stability between SA and delivery in patients treated by phenylephrine.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, only 4 other studies 6,7,21,22 have compared the time course of CO between parturients treated by norepinephrine or phenylephrine during elective cesarean delivery. In a double-blinded randomized trial comparing computer-controlled infusion of norepinephrine or phenylephrine in 104 parturients, 6 CO (measured by the suprasternal Doppler method) and HR were higher in the norepinephrine group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations